Pengaruh Variasi Jenis Pelarut Dan Jenis Cat Sebagai Inhibitor Korosi Terhadap Laju Korosi Baja Astm A36 - Dewi Amalia; Kosjoko, Kosjoko; Nely Ana Mufarida (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effect of solvent variations in paint mixtures on the corrosion rate of ASTM A36 steel in a seawater immersion environment. ASTM A36 steel is widely used in construction and marine structures but is susceptible to corrosion due to exposure to seawater containing high concentrations of chloride ions. One commonly applied method for corrosion control is surface coating using paint as a physical inhibitor, whose effectiveness is strongly influenced by the type of solvent used. The solvent variations investigated in this study include thinner A special, thinner A ordinary, and thinner B. The research employed a quantitative experimental method. ASTM A36 steel specimens were coated with paint using a 50:50 ratio of paint to solvent and then immersed in natural seawater for 30 days. The corrosion rate was determined using the weight loss method. In addition, surface morphology observations after immersion were conducted using an optical microscope to identify the type and severity of corrosion damage. The results indicate that variations in solvent type within the paint mixture affect the corrosion rate of ASTM A36 steel. Certain combinations of paint and solvent were able to reduce the corrosion rate more effectively than others. These differences are attributed to the solvent’s ability to form a protective coating with good adhesion and uniformity on the steel surface. Therefore, selecting an appropriate solvent type can enhance the effectiveness of paint coatings as a corrosion control method for ASTM A36 steel in marine environments.